PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH SIMPEDA BANK JATENG (Studi Kasus Pada Bank Jateng Cabang Pemuda Semarang) - Safond Agung Perwira; Hari Susanta Nugraha; Sri Suryoko (Universitas Diponegoro, 2015)
The development of the banking sector has led to intense competition. Competition requires each bank vying to provide good service to its customers, both in the quality of the service-oriented customer satisfaction or customer (customer satisfaction). Therefore, a bank manager in achieving the objectives of the company must be able to determine the appropriate competitive strategy in creating customer satisfaction and perform management functions well.This study aims: To determine the influence of tangibility, reliability, responsiveness, assurance, empathy toward customer satisfaction Simpeda Bank Branch Pemuda Semarang Central Java and to determine the effect of customer satisfaction on customer loyalty Simpeda Bank Branch Pemuda Semarang Central Java.This type of research is quantitative research, with data collection through questionnaires. The sampling technique used judment sampling technique, the sample of 100 people who are customers of Bank Branch Youth in Semarang, Central Java. The method of analysis used in this study is the regression analysis, the validity and reliability.Based on the analysis, the conclusion is: There is the influence of tangibility, reliability, responsiveness, assurance, empathy, to customer satisfaction Simpeda Bank Branch Pemuda Semarang Central Java. There is the effect of customer satisfaction on customer loyalty Simpeda Bank Branch Pemuda Semarang Central Java.Suggestions that can be put forward in this study include the following: Should the Bank Branch Pemuda Semarang Central Java can further improve the quality of the fifth dimension pelayannnya as proven effect on client satisfaction and customer loyalty. This can be done by: adding facilities such as ATM, increasing the comfort of the lounge for example air conditioner cooler, do trining officers so that they can be more accurate in providing services and information to customers, rapid response in response to the complaint, the bank employee to be more concerned about the customer and perform up to date technology that increases customer satisfaction. In a subsequent study with a similar topic can be increased moderating variables or other variables that affect customer satisfaction.